The Impact of Using the Pregnancy and Baby Tracker Application on Anxiety Among Pregnant Mothers - Sartika Sartika; Azrida Machmud; Adelia Adelia; Nur Emizah; Andi Sani (Pancasakti Journal Of Public Health Science And Research, 2025)
In today's digital era, information technology has great potential to help reduce anxiety in pregnant women by providing accurate and easily accessible information. One of the innovations that has been developed is a mobile application specifically designed to support the health of pregnant women and babies. The purpose of this study was to analyze the effect of using the pregnancy and baby tracer application on the anxiety of pregnant women in the Pangkajene Health Center work area, Sidenreng Rappang Regency. The type of research used was a quasi-experimental study. The design used was a pretest-posttest with control group design. The population was all pregnant women who made pregnancy visits at the Pangkajene Health Center and a sample of 52 pregnant women with a classification of 26 pregnant women who were given pregnancy and baby tracer application intervention and 26 pregnant women only received ANC services. Anxiety was measured using the HARS questionnaire. Data analysis used Paired T-Test and Mann Whitney. The results of this study showed a decrease in anxiety scores after receiving pregnancy and baby tracer application intervention. The conclusion of the study is that there is an influence of the use of the pregnancy and baby tracer application on the anxiety of pregnant women in the Pangkajene Health Center work area.